Pola spasial-temporal kejadian demam berdarah dengue di kota Palopo - Sitti Ashlihah; Citra Indriani; Lutfan Lazuardi (Berita Kedokteran Masyarakat (BKM), 2016)
Spatial-temporal pattern of dengue hemorraghic fever in the city of PalopoPurposeThis study was conducted to know comparison of spatial-temporal pattern and to analyze dengue hemorraghic fever supporting factors in the city of Palopo. MethodsThis study used descriptive analytic survey with ecological approach and case control design. Dependent variable was dengue hemorraghic fever event, independent variables were population density, free number flick, rainfall, vegetation density, building density, housing density, wire netted ventilation, education, work, 3M habit, hanging clothes habit, and using anti mosquito. Total sampel were 391 respondent. ResultsThere were correlation between population density, wire netted ventilation, mosquito larva existence, 3M habit, hanging clothes, and using anti mosquito with dengue hemorraghic fever occurrence in the city of Palopo and cases distribution pattern grouped at densely populated district, with medium-high rainfall, medium vegetation density, and to all building density group. ConclusionCases distribution pattern affected by population density, medium-high rainfall, medium vegetation density, and to all building density group.